Detection of cathepsin D in ewe’s milk by Western Blotting method - Iva Dolenčić Špehar; Franjo Martinković; Jasmina Havranek; Albert Marinculić; Milna Tudor Kalit; Samir Kalit (Mljekarstvo)
Milk contains about 70 indogene enzymes, while only twenty of them were investigated. One of the less explored is the milk enzyme cathepsin D, proteolytic enzyme located in the lysosomes, which are an integral part of the somatic cells whose number varies depending on the animal’s health. Unlike cow’s milk, in ewe’s milk the presence of cathepsin D was not determined, which could affect the production of dairy products, especially cheese, which are traditionally produced in Croatia and Mediterranean. This paper shows the presence of cathepsin D and its forms in ewe’s milk by modified Western Blotting method. The analysis confirmed the presence of procathepsin D, mature and heavy chain of cathepsin D. Pseudocathepsin D and light chain of cathepsin D were not detected.